Zinfandel : a history of a grape and its wine - Sullivan, Charles L. (Charles Lewis), 1932- (California studies in food and culture, 2003)
The Zinfandel grape--currently producing big, rich, luscious styles of red wine--has a large, loyal, even fanatical following in California and around the world. The grape, grown predominantly in California, has acquired an almost mythic status--in part because of the caliber of its wines and its remarkable versatility, and in part because of the mystery surrounding its origins. Charles Sullivan, a leading expert on the history of California wine, has at last written the definitive history of Zinfandel. Here he brings together his deep knowledge of wine with the results of his extensive research.